Are we failing them? : an analysis of the New Zealand criminal youth justice system : how can we further prevent youth offending and youth recidivism? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Policy at Massey University, Auckland, New Zealand - Johnson, Charlotte (Massey University, 2015)
Youth crime is a prominent social issue in New Zealand that causes emotional and physical harm and loss to the numerous victims. This research provides an analysis of the current youth criminal justice system in New Zealand, beginning with a timeline of the history and evolvement of the youth justice system to illustrate how New Zealand has arrived at the present system. The drivers of youth crime and youth involvement in criminal offending were found to be initially born from a lack of engagement with education; neurological disorders; learning difficulties and mental illness; as well as the impact of young people’s childhood, which can include exposure to family violence; drug and alcohol abuse. Comparative policy evaluation was applied with comparative methodology and comparative cross national research to undertake an analysis of the youth justice system in New Zealand. International comparisons were used to discover plausible and practical improvements to the current youth justice system in New Zealand. The OECD countries used in the comparative analysis included Canada, Scotland, England & Wales, United States and Austria, who between them have significantly diverse and contrasting youth justice models ranging from welfare, care and protection centred models, to community-based rehabilitation models; preventative education and support to punitive models in their response to youth crime. ii It was found that several aspects of New Zealand’s current youth justice system function well when compared internationally. However, the comparative analysis also highlighted that New Zealand’s youth justice system presents a problematic gap in both the sheer lack of preventative methods in response to youth offending as well as community support during the rehabilitation stage. A number of policy recommendations are included within this report in response to the present shortcomings of the existing youth justice system in New Zealand. These policy recommendations provide practical solutions; adopting a preventative policy focus with plausible improvement suggestions to the existing youth justice system. The objectives are to ameliorate the youth justice system to better support youth offending and youth recidivism.
Keywords: Juvenile delinquency; Prevention; Juvenile justice, Administration of; Family social work; New Zealand; Research Subject Categories::LAW/JURISPRUDENCE::Criminal law